2011
DOI: 10.1111/j.1440-1800.2010.00501.x
|View full text |Cite
|
Sign up to set email alerts
|

Demoralization and remoralization: a review of these constructs in the healthcare literature

Abstract: Demoralization and remoralization: a review of these constructs in the healthcare literature Development of the constructs of demoralization and remoralization began in the psychiatric literature in the 1970s when a psychiatrist in the USA observed a pattern of characteristics in people referred to him for depression, which he believed, was not depression. These characteristics included hopelessness, helplessness, isolation, low self-esteem and despair. Such characteristics are often termed existential distres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Clarke and Kissane [7] define demoralization as an affective state of loss of meaning and hopelessness, with cognitions of helplessness and personal failure, subjective incompetence, and social alienation. Research has repeatedly applied this concept to severe medical illness, emphasizing that demoralization is essentially characterized by an entrapped feeling that “nothing can be done” and a subsequent loss of hope and meaning, while the two core symptoms of major depression, anhedonia and loss of interest, are typically not present [8][11]. Factor analytic studies support the conceptual and clinical separation of demoralization and major depression in cancer patients [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…Clarke and Kissane [7] define demoralization as an affective state of loss of meaning and hopelessness, with cognitions of helplessness and personal failure, subjective incompetence, and social alienation. Research has repeatedly applied this concept to severe medical illness, emphasizing that demoralization is essentially characterized by an entrapped feeling that “nothing can be done” and a subsequent loss of hope and meaning, while the two core symptoms of major depression, anhedonia and loss of interest, are typically not present [8][11]. Factor analytic studies support the conceptual and clinical separation of demoralization and major depression in cancer patients [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…The loss of hope provides a focal point for social work interventions that seek to regenerate hope to reestablish coping. Cognitive-behavioral therapy has been shown to be less effective for severe demoralization, but certain cognitive strategies have the potential to restore hope and a renewed sense of purpose (Connor & Walton, 2011;Snyder, 1999). Snyder (2000) suggested that people who are hopeful and cope well in adversity have the capacity to find alternative hopeful futures.…”
Section: Interventionsmentioning
confidence: 99%
“…Effective demoralisation management includes the early reduction of stressors, the detection of negative emotions, and the provision of mental and spiritual care necessary to reinstate patients’ hope, self‐respect, and meaning of life (Connor & Walton, ; Thangathurai et al., ). Because a “sense of failure” is the worst domain of demoralisation before and after surgery, strategies should be designed to empower patients such as engaging with the patient throughout the medical decision‐making process to promote a sense of control, encouraging them to perform their own daily activities to decrease the perception of dependence, and addressing the importance of family for their support in helping patients solve life problems and not feel alone.…”
Section: Relevance To Clinical Practicementioning
confidence: 99%
“…Demoralisation syndrome differs from depression with regard to its signs, causes and treatments (Tecuta et al., ). Demoralisation syndrome management includes psychotherapy and spiritual treatments that emphasise re‐moralisation to increase the patient's feelings of dignity and self‐worth (Connor & Walton, ); conversely, depression treatments include antidepressants, cognitive behavioural therapy and physical activity (Lichtman et al., ). Therefore, this study investigated the incidence and contributors to demoralisation syndrome among patients before and after cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%